A (time) series of unfortunate events: Structural change, globalization, and the rise of occupational injuries - Amalavoyal Chari (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
There is a dearth of evidence on the evolution of occupational health in the developing world and on the extent to which it has been influenced by (1) the pattern of structural transformation in these economies and (2) integration with global markets. In this study, I compile a rich database on workplace injuries in India covering a five-decade period. I use these data to examine trends in the rate of occupational injuries and show that the rate of occupational injuries began trending sharply upwards starting in the 1990s. This phenomenon does not appear to reflect sectoral shifts in employment arising from structural transformation but rather increases in injury rates in non-agricultural sector. By combining disaggregated industry-level injury data with quasiexperimental variation in exposure to key policy reforms, I find that the uptick in injury rates can at least partially be explained as a result of changes in the policy landscape in the 1990s that exposed Indian manufacturing to international markets.
Keywords: J28; J81; O14; O10; 330; structural change; occupational health; workplace safety; globalization; India